2016
DOI: 10.1186/s12966-016-0372-z
|View full text |Cite
|
Sign up to set email alerts
|

Social cognitive theory mediators of physical activity in a lifestyle program for cancer survivors and carers: findings from the ENRICH randomized controlled trial

Abstract: BackgroundDespite increasing numbers of cancer survivors and evidence that diet and physical activity improves the health of cancer survivors, most do not meet guidelines. Some social cognitive theory (SCT)-based interventions have increased physical activity behavior, however few have used objective physical activity measures. The Exercise and Nutrition Routine Improving Cancer Health (ENRICH) randomized controlled trial reported a significant intervention effect for the primary outcome of pedometer-assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
2
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 74 publications
(92 reference statements)
4
26
2
2
Order By: Relevance
“…Based on research examining correlates of MVPA, perceived social support was expected to be positively associated with LPA and higher unsupportive partner response to cancer was expected to be negatively associated with LPA. Instead, results revealed no significant association of perceived social support and LPA.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on research examining correlates of MVPA, perceived social support was expected to be positively associated with LPA and higher unsupportive partner response to cancer was expected to be negatively associated with LPA. Instead, results revealed no significant association of perceived social support and LPA.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, social motivation should be provided in behaviour change interventions. Goal-setting can be self-set, assigned or collaborative (32,33). Therefore, including goal-setting, having an attainable goal, conducting self-monitoring and providing feedback have been recognised as requirements for behaviour change support (34).…”
Section: Persuasive Systems Designmentioning
confidence: 99%
“…Many theoretical constructs have been tested as mediators of change and results are not consistent. Self-efficacy, [10,16,20] Social support, [10] goal setting, [16,19] and behavioral processes [15,21] have been found to mediate change in physical activity behavior in some studies, although other studies have not found support for some of these constructs [12,13,16,19]. It is important to note that the samples included in these studies are quite diverse (i.e., older adults, pregnant women, cancer survivors, healthy populations).…”
Section: Introductionmentioning
confidence: 96%
“…Although significant progress has been made in understanding how physical activity interventions exert their effects, [10][11][12][13][14][15][16][17][18][19][20][21] much work remains. Many theoretical constructs have been tested as mediators of change and results are not consistent.…”
Section: Introductionmentioning
confidence: 99%